Marhaenis Muhammadiyah: ajaran dan pemikiran K. H. Ahmad Dahlan / Abdul Munir Mulkhan ; penyunting Sigit Suryanto - ABDUL MUNIR MULKHAN; Sigit Suryanto (Galang Pustaka, 2013)
323 hlm. : ilus. ; 23 cm. (2 eks.)